2003
DOI: 10.1159/000072474
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Lymphangiomatosis of the Craniocervical Spine in Conjunction with a Chiari I Malformation

Abstract: Lymphangiomatosis of the bone is rare. The axial as well as appendicular skeleton may be affected. Neurosurgical consultation may be called for several reasons: (1) lesions involving the calvarium and/or spine; (2) nondiagnostic biopsies from more accessible and less morbid locations, and (3) persistent CSF leak and/or recurrent meningitis. Thus, it is important for the neurosurgeon to be familiar with this disease entity and consider it in the differential diagnoses of multifocal lytic lesions of the axial sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…[1][2][3][4] Chiari I malformation has also been reported in 7 patients with Gorham or related diseases, though the relationship between the 2 conditions is not clear. [5][6][7][8] We describe a child with Gorham disease who was initially treated for Chiari I malformation, which was, in retrospect, secondary to intracranial hypotension from a CSF fistula between a lumbar nerve root sleeve and a lymphatic malformation.…”
mentioning
confidence: 99%
“…[1][2][3][4] Chiari I malformation has also been reported in 7 patients with Gorham or related diseases, though the relationship between the 2 conditions is not clear. [5][6][7][8] We describe a child with Gorham disease who was initially treated for Chiari I malformation, which was, in retrospect, secondary to intracranial hypotension from a CSF fistula between a lumbar nerve root sleeve and a lymphatic malformation.…”
mentioning
confidence: 99%
“…It has been suggested that the etiology of the Chiari malformation in these cases could perhaps be explained by the softness of the involved bone and settling of the occiput [6]. We describe the first case of a Chiari I malformation in a Gorham’s patient without clear documentation of skull base or cervical involvement.…”
Section: Discussionmentioning
confidence: 88%
“…4 Jea et al discuss treatment of a 4-year-old girl with lymphangiomatic lesions throughout the skull base and upper cervical vertebrae. 11 She presented with headaches and ear pain, and demonstrated widespread lytic lesions as well as an acquired Chiari I malformation. The team performed a decompressive suboccipital craniectomy and C-1 laminectomy, with improvement in head and neck pain and no signs of craniocervical instability.…”
Section: Discussionmentioning
confidence: 99%